Theoretical Linkage between Corporate Social Responsibility and Corporate Reputation - Rashedul Hasan; Tee Mei Yun (Universitas Pasundan, 2017)
In today’s corporate world, Corporate Social Responsibility (CSR) is becoming a significant field of study for all businesses as its notion has increased attention of both academics and practitioners. Secondary sources of data are utilized using document analysis method to understand the relationship between Corporate Social Responsibility (CSR) and corporate reputation (CR). Five papers are selected from Science Direct which covers the time frame of 2012 until 2017. Evidence indicates that there is a positive, direct and significant relationship between CSR and CR. This paper contributes to the understanding of interrelations between CSR and CR. Practitioners can use the result of this study as a foothold to strengthen the integration of CSR and take advantage of synergies between CSR and CR. The value of paper resides in making this rather under-researched literature on the relationship between CSR and CR be more accessible for both scholars and practitioners.